Influence of geographical space on the strength of the breathing muscles of elderly residents in the rural and urban areas of the high hinterland of Paraiba - Mikaelly Gomes Nóbrega; Ankilma do Nascimento Andrade Feitosa; Rafaelle Cavalcante de Lira; Elisangela Vilar de Assis; Sávio Benvindo Ferreira; Ubiraídys de Andrade Isidório (Journal of Novel Physiotherapy and Physical Rehabilitation - Peertechz Publications, 2023)
Introduction: We observe, in the aging process, important functional changes in our organism that can be influenced by the environment in which we are inserted.  Objective: To comparatively evaluate the respiratory muscle strength of elderly people in rural and urban areas.  Methodology: This is a cross-sectional and analytical research, whose data were analyzed quantitatively, which was carried out with elderly people living in the urban area, registered at the Social Assistance Reference Center (CRAS), and in the rural area, at the Urban Social Center (CSU) in Sousa city, in Paraíba state. The sample was random and for convenience. An anthropometric and respiratory muscle strength assessment was carried out. Individuals aged 60 years or older, of both sexes, who had good mental conditions to answer the questions and could walk were included, and those who had cognitive deficits, visual, cardiac, respiratory, neurological problems, and neoplasms were excluded.  Results: 84 elderly people participated in the research, of both sexes, divided into two groups: urban area (n = 43) and rural area (n = 41). With regard to respiratory muscle strength, when comparing the maximal Inspiratory Pressure (IPmax) with the maximal expiratory pressure (PEmax) of the elderly in relation to the place of residence, there were no statistically significant results in the evaluated variables (p > 0.05).  Conclusion: There was no statistically significant difference in the respiratory muscle strength of the elderly evaluated at the expense of the habitat.